CHARACTERIZATION OF CHARACTERS IN SALAM SADIGZADEH'S NOVEL “THERE IS A BEAUTIFUL WOMAN IN OUR VILLAGE” - Гюнель Сафарова, (KONFERENSIYALAR, 2025)
Abstract.    One  of  Salam  Sadigzadeh's  works,  which  has  an  interesting  plot  line,  is distinguished by its sincere description of events, and talks about the spiritual and moral qualities of young people, is the novel "There is a beautiful woman in our village", which consists of 15 short stories. Although the novel has been discussed in various articles, it has not been studied in detail. From  this  perspective,  the  study  of  the  novel  is  both  relevant  and  interesting.  The  events  that happen to a woman,  their negative effects that have on her life, their negative marks left on her character, the betrayal of the wife to a husband who lost his eyes in the war, the killing of a mother the baby who thought she was his child, etc. issues are reflected in the novel.